Characterisation and quantification of microstructure, physicochemical and functional properties of oven and forced convection continuous tumble roasted cereal grains - Schoeman, Letitia (Stellenbosch : Stellenbosch University, 2017)
Thesis PhD(Food Sc)--Stellenbosch University, 2017.